Devenir (temporairement) « frontiste ». Ce que les rapports de genre et de classe disent du FN à partir d’en bas - Margherita Crippa (Terrains/Théories)
Through the reflective analysis of an ethnographic experience in a group of female and male activists of the French Front National, this contribution shows the structuration dynamics of a political group at the crossroads of several power relations. This work finds its raison-d'être in two methodological and analytical principles. First, the objectification of fieldwork relations fully contributes to the understanding of one or more aspects of the object under study, by highlighting some of its structural properties, its functioning, or its symbolic economy. Furthermore, embracing the intersectionality viewpoint allows to systematically reflect upon the articulation of several social dimensions in the production of fieldwork relations, and, consequently, the effects of this articulation in the understanding of the social processes that produce groups. Therefore, this contribution questions the stakes of fieldwork relations established in a localized FN environment at a key moment of this party’s history. Along with the arrival of Marine Le Pen at the head of the FN, the party has been increasingly integrating the French political field. While the FN staff, starting from its female president, is meant to be partially new, younger, feminized, and concerned to display an allegedly more welcoming façade of the party, I intend to question the social relations which structure the organization behind its facade. A certain social proximity with the respondents and the rare resources, in connection with my femininity, that I was able to offer them, determined the degree of openness as well as the course of the fieldwork, and defined the modalities of my commitment. This has allowed me to understand the various sources of commitment that make (and unmake) the party from below. My place within the group of female and male activists and the way I had to undertake some militant tasks demonstrate how gender and class relations, commonly harmful to women, structure the group of female and male activists by creating it almost from scratch, and reinforce the hierarchical hegemony of certain actors.